Rationale for assessing digital transformation of business processes of the organization by indicators of financial stability - V. V. Manuilenko; V. A. Tsarevsky; G. A. Ermakova; V. V. Tishina; K. O. Nikitina (Вестник Северо-Кавказского федерального университета)
Introduction. In the conditions of uncertainty and limited financial resources, on the one hand, it is financially stable organizations of small, medium, large businesses that can ensure full-fledged digital transformation processes, and, on the other hand, digitalization has a positive effect on the business processes of the organization, thereby increasing its financial stability, indicating the relationship, interdependence of these processes, which must be assessed by special indicators characterizing the financial stability of the organization. Goal. The study aims to substantiate the need to assess the digital transformation of business processes in the organization by indicators of financial stability, both in terms of influence on their state and predetermination. Materials and methods. In the course of the research, the works of Russian authors have been studied, indicating the need for the integrated use of digital tools, reducing the risks of the financial sector. There is a focus on the traditional accounting approach to assessing the financial stability of an organization, the process approach, digital transformation within the framework of the process approach, and correlation of the traditional approach to assessing digital transformation with the expert assessment. The study highlights the key components that determine the effectiveness and focus of a business process. Results and discussion. In the theoretical area of the study: the main features inherent in the concept of "financial stability" of an organization are identified; the parameters for comparing the main types of targeted programs – digital transformation of business processes – are determined; the essence of reengineering by special characteristics is presented; the dual nature of the financial stability of an organization is argued. In the methodological area of the study: the traditional, process approaches to assessing the financial stability of an organization are presented. It is substantiated that the synthesis of the traditional, process approaches to assessing the financial stability of an organization is a key area of its assessment in conjunction with digital transformation. The main types of targeted programs are defined and characterized – digital transformation of business processes. Conclusion. As a result, the theoretical and practical significance of assessing the digital transformation of an organization's business processes using financial stability indicators is substantiated, which expands the study of the theoretical and methodological aspects of its assessment in the context of digitalization.